Back Cover: Solution Observation of Dimerization and Helix Handedness Induction in a Human Carbonic Anhydrase–Helical Aromatic Amide Foldamer Complex (ChemBioChem 8/2016). (5th April 2016) - Jewginski, Michal; Fischer, Lucile; Colombo, Cinzia; Huc, Ivan; Mackereth, Cameron D.
Abstract : The back cover picture shows a molecular study in the solution state of a foldamer–protein complex. NMR spectroscopy measurements show that the attached helical foldamer (depicted by an extended right hand) is dynamic in solution. Circular dichroism nevertheless confirms a preference for the right‐handed enantiomer within the complex. This handedness, and an ability to dimerize, is shared with the solid‐state crystal structure, although in solution the dimerization is found to be buffer dependent, as shown by the foldamer–protein handshake only in the bottom panel. More information and molecular details of the complex can be found in the full paper by I. Huc, C. D. Mackereth et al. onpage 727 in Issue 8, 2016 (DOI:10.1002/cbic.201500619 ).